Adopting sea water reverse osmosis desalination technologies for sustainable development: lessons learnt from Algiers Science and Technology for membranes 2023 workshop - Ouali, S.; Doucoure, A. (Frontiers in Membrane Science and Technology, 2024)
The city of Algiers hosted the workshop on Science and Technology for Membranes from May 30 th to June 1 st , 2023 -STM 2023, held in Algeria. The main topics focused on Reverse Osmosis (RO) desalination technologies, decentralized autonomous systems, wastewater recycling for circularity, and the effects of green membrane processes on socio-economic growth. This review examines the influence of global trends and instabilities (i.e., climate change, disrupted supply chain platforms, natural disasters) on the steady supply of freshwater. The implementation of RO desalination solutions and their sustainability are assessed based on resiliency factors, which is helpful to screen water treatment alternatives based on technological benefits, ecological safety and environmental protection. Key takeaways from this study call for rolling out local membrane production capabilities, promoting the benefits of autonomous decentralized treatment systems, prioritizing innovative solutions to reduce greenhouse gas emissions, and for developing RO-specific equipment recycling infrastructures. Implementing these new tactics can lead to mitigate water scarcity and enable a sustainable deployment of desalination membrane technologies in Algeria and its region.